SEJARAH EVOLUSI SHOPPING MALL - Sari, Sriti Mayang (Institute of Research and Community Outreach - Petra Christian University, 2010)
The development ofmalls or shopping centers can be observed through the various facilities and functions that do not only serve as places to shop but also offer increasing modes of entertainment such as cinema theatres, fashion, food court, indoor playgrounds and exhibition spaces which are the results of a long evolution. The aim of this paper is to describe the development of the historical evolution ofmall, starting from the background of shopping processes until the early establishment of shopping centers and aspects of influence. These processes will continue to evolve in future.